Relationship Of Duration And Frequency Of Playing Online Games With Emotional Mental Problems In Adolescents - Emi sri wahyuni; Fatmawati; Edison Siringoringo (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
The duration of playing online games is the length of time someone plays online games. While the frequency is playing online games, that is the level of frequent use of online game games in a day, even per week. The purpose of the study is to find out the relationship between the duration and frequency of playing online games with emotional and mental problems in adolescents in junior high school 19 bulukumba. Research method this study is a type of descriptive correlation research with a crossectional approach. A sample of 49 respondents from all adolescent populations. While the frequency is playing online games, that is the level of frequent use of online game games in a day, even per week. Based on the results of this test, the value of ρ = 0.006 < α = 0.005. Thus, based on the final results, it can be concluded that